Strategi 6 Keluarga sebagai Pengelola pada Pemandian Aek Rangat Butar di Desa Banualuhu Kecamatan Pagaran Kabupaten Tapanuli Utara - Indriani Lubis (Jurnal Antropologi Sumatera, 2023)
This study aims to determine the background of livelihood transition in 6 families as managers of Aek Rangat Butar baths and to determine the socioeconomic conditions in 6 families before and after diving in livelihoods as managers of Aek Rangat Butar baths in Banualuhu Village, Pagaran District, North Tapanuli Regency. This study uses a qualitative research method with a descriptive approach with a focus of research in the Aek Rangat Butar bath in Banualuhu Village, Pagaran District, North Tapanuli Regency. The collection techniques in this research use observation, interviews, literature study, and documentation, with data analysis techniques using three activities, namely data reduction, data presentation, and drawing conclusions. the results of the research are as follows: Switching the community livelihood system from farmers to managing the aek rangat buteng in Banualuhu village because 6 families who as informants are farmers in Banualuhu village all implement survival strategies and experience livelihood transition to bathing managers Aek Rangat, this is done to maintain life, meet basic family needs and improve family living standards.